(untitled) (American Journal of Islam and Society, 1987)
Slavery is one of the most controversial and arresting topics in human history. The question of Islam in relation to slavery has been an issue of concern among scholars for a long time. It became a question in which many Orientalists found a convenient gap to pass through in their attacks against the system of governance and justice in Islam. This self-righteous criticism against the attitude of Islam towards slavery is part of a long Western tradition of scholarship based on stereotyping, overstating, and selectivity of Islam in particular and the Orient in general. Most of the time, the statements of these scholars are presented in a sugar-coated style of language that is more dangerous than if they were presented in a critical, open, and direct language. Thomas Carlyle, Renan, Goldziher, Macdonald, von Grunebaum, Gibb and Bernard Lewis are good examples and representatives of this traditi0n.l The aim of this article is to use ijtihad, or informed intellectual effort, to show through textual and historical evidence that Islam, in its battle for justice, which is identical to human rights, fought against slavery and initiated a humane and practical plan for its abolition. Only deviation from Islam prevented elimination of slavery within the first few decades of Islam. In Arabia itself within forty years, except for temporary prisoners of war, slavery had disappeared. We shall begin with a brief historical survey of the institution of slavery before Islam. The body of this article will concentrate on discussion and analysis of some related texts from the Qufan and the Hadith as well as some historical data that reflect the practical attitude of devoted Muslims towards slavery and slaves. The attitude of Islam towards race, color, and slavery in the context of the trans-Saharan slave trade are two issues that this paper will deal with since they have a direct bearing on the question of slavery in Islam ...